Changes in Haemostatic Factors and Activation Products after Exercise in Healthy Subjects with Different Ages - van den Burg, P J M; Hospers, J E H; van Vliet, M; Mosterd, W L; Bouma, B N; Huisveld, I A (Thrombosis and Haemostasis, 1995)
We studied exercise-induced changes in coagulation and fibrinolytic factors and activation products in different age categories. Thirty-eight sedentary males, divided in three age categories (cats I-III; 20-30, 35-45 and 50-60 y) were subjected to a standardized exercise test.Pre-exercise levels (cats I-III resp) of FVII:c (105 ± 5, 121 ±6 and 123 ± 7% NP), fibrinogen (2.35 ± 0.12, 2.55 ± 0.10 and 2.66 ± 0.09 mg/ml), prothrombin activation fragment F1+2 (0.80 ± 0.10,0.80 ± 0.11 and 1.22 ±0.16 nM), t-PA (5,2 ± 0.6, 9.2 ± 1.0, 8.6 ± 1.2 ng/ml) and PAI-1 (42.8 ± 7.5, 67.6 ± 7.6, 62.2 ± 10.9 ng/ml) showed differences that seemed related to age. Regression analysis revealed associations with anthropometry (FVII:c, fibrinogen, F1+2, t-PA, PAI-1) rather than with age.Exercise-induced changes in coagulation (increase in von Wille-brand factor and FVIII:c and a shortening of APTT) and fibrinolytic potential (increase in t-PA and u-PA) were of comparable magnitude for the three age categories. Hardly any change in F1+2 (6%) was observed, while thrombin-antithrombin complexes (93%), plasmin-antiplasmin complexes (79%) and D-dimer (77%) almost doubled during maximal exercise.We conclude that anthropometric differences play a more significant role than age on constitutive levels of haemostatic factors in participants up to 60 years of age. The magnitude of exercise-induced changes is comparable in the age categories under study, and simply superimposed on constitutive (pre-exercise) levels. Clear evidence for prothrombin activation is lacking, but plasmin formation is enhanced during exercise.